The Islamic Economic Perspective on the Practice of Partnership Cooperation Contracts - Yesi Novrianti; Wargo; Zaenal Abidin (Journal of Economics and Social Sciences (JESS), 2025)
Partnership cooperation contracts constitute one of the essential instruments within the Islamic economic system, aiming to realize justice, balance, and mutual welfare among the contracting parties. Partnership practices are widely found across various economic sectors, including trade, agriculture, services, and Islamic finance. This article seeks to examine the Islamic economic perspective on the practice of partnership cooperation contracts through a literature-based approach. The method employed is a literature review of classical and contemporary fiqh al-muʿāmalāt texts, scholarly journals, fatwas issued by authoritative institutions, and regulations related to Islamic economics. The findings indicate that Islamic economics provides a clear normative framework for partnership contracts, such as musyārakah, muḍārabah, muzāraʿah, and musāqah, which emphasize the principles of justice, transparency, honesty, and the proportional sharing of risks and profits. Nevertheless, contemporary practices continue to exhibit deviations from these principles, particularly in terms of unequal bargaining positions and imbalanced risk allocation. Therefore, strengthening the understanding of Islamic contractual principles and enhancing the supervision of their implementation are crucial to ensuring partnerships that are consistent with Islamic economic values